2005
DOI: 10.1128/jb.187.21.7351-7361.2005
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipids Modulate Swarming Motility Patterns ofPseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is capable of twitching, swimming, and swarming motility. The latter form of translocation occurs on semisolid surfaces, requires functional flagella and biosurfactant production, and results in complex motility patterns. From the point of inoculation, bacteria migrate as defined groups, referred to as tendrils, moving in a coordinated manner capable of sensing and responding to other groups of cells. We were able to show that P. aeruginosa produces extracellular factors capable of modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
463
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(489 citation statements)
references
References 54 publications
21
463
1
4
Order By: Relevance
“…Recently, it has been suggested that the precursor of rhamnolipids, 3-(3-hydroxyalkanoyloxy)alkanoic acid, is required for surface wettability and rhamnolipids for modulating Ps. aeruginosa swarming behavior (29,31). Our results add a class of biosurfactant molecules to this list.…”
Section: Oh-(slc)-hsl Produced By Cini In R Etli Decreases Viscosmentioning
confidence: 99%
“…Recently, it has been suggested that the precursor of rhamnolipids, 3-(3-hydroxyalkanoyloxy)alkanoic acid, is required for surface wettability and rhamnolipids for modulating Ps. aeruginosa swarming behavior (29,31). Our results add a class of biosurfactant molecules to this list.…”
Section: Oh-(slc)-hsl Produced By Cini In R Etli Decreases Viscosmentioning
confidence: 99%
“…Swarming is dependent on the combination of the polar flagellum, type IV pili and rhamnolipid production (Caiazza et al, 2005;Kohler et al, 2000). This type of motility is almost completely absent in the oxyR mutant grown on CAA medium (Fig.…”
Section: Oxyr Is Required For Swarming Motility and Rhamnolipid Produmentioning
confidence: 99%
“…The CSF samples were taken from different individuals than those who provided the serum samples. The average age of AD patients was 75 years (56-85), of MCI patients 70 years , and of controls 73.3 years (68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). Each sample was assayed in duplicate.…”
Section: The Elisa Methods For Rls Immunodetection In Csf From Ad Patimentioning
confidence: 99%